“Outside in”: Global demand heterogeneity and dynamic capabilities of multinational enterprises - Zhang, Xiao; Xie, Luqun; Li, Jiatao; Cheng, Li (Journal of International Business Studies, 2022)
We conceptualize the dynamic capabilities of multinational enterprises (MNEs) as learning and adaptation capabilities that address the pressure of global integration and local responsiveness. Complementing the extant literature on dynamic capabilities, which is focused on the supply side, our study draws attention to the demand-side influences, especially in terms of global demand heterogeneity. We propose that global demand heterogeneity provides pressures and opportunities for MNEs to learn and adapt and, thus, positively relates to the development of MNE dynamic capabilities. However, external sources per se may be insufficient. Firm-specific advantages, particularly human capital (at the managerial and employee levels), facilitate the internalization of external knowledge and pressure into the development of dynamic capabilities. An empirical study of Chinese multinational service firms strongly supports these arguments.